Anti-Oxidant and Vitamin C Activity Test of Horseganik Clay Mask Products, Sumbawa Horse Milk - Munandar, Imam (Journal of Tropical Animal Science and Technology, 2024)
The growth of the cosmetics market in Indonesia is also projected to increase by 7% in 2021 (Databoks, 2021). "The growth of the cosmetics industry in 2017 grew 6.35%, which originally increased from 153 companies to 760 companies, and exports reached US$519.99 million compared to the previous year which was US$470.3 million. Currently, many consumers are interested with a wide selection of cosmetic products to support their appearance. The content of Sumbawa Wild Horse Milk contains probiotics and lactic acid bacteria in horse milk which can kill bad bacteria that cause acne on the face. The results of the study proved that the milk of the Sumbawa wild horse was effective as an anti-bacterial against Staphylococcus epidermidis (one of the bacteria that causes acne). The results of the study, the content of Vitamin C horse clay mask is 64.8% which corresponds to the daily requirement of vitamin C commonly known as the RDA (Recommended dietary allowance) of vitamin C which is 60 mg or the equivalent of an orange, for anti-oxidant activity IC50 10.88 ppm contained in the horsegenic mask able to reduce aging and other skin diseases caused by a lack of nutrient intake for the skin.